European white-collar crime exploring the nature of European realities - Lord, Nicholas (Bristol University Press, 2021)
From corporate corruption and the facilitation of money laundering, to food fraud and labour exploitation, European citizens continue to be confronted by serious corporate and white-collar crimes. Presenting an original series of provocative essays, this book offers a European framing of white-collar crime. Experts from different countries foreground what is unique, innovative or different about white-collar and corporate crimes that are so strongly connected to Europe, including the tensions that exist within and between the nation-states of Europe, and within the institutions of the European region. This European voice provides an original contribution to discourses surrounding a form of crime which is underrepresented in current criminological literature
Title from publisher's bibliographic system (viewed on 13 Apr 2023)
Keywords: Commercial crimes / Europe; White collar crimes / Europe; Aufsatzsammlung